Western Foundations of the Caste System - Fárek, Martin; Jalki, Dunkin; Pathan, Sufiya; Shah, Prakash (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book argues that the dominant descriptions of the 'caste system' are rooted in the Western Christian experience of India. Thus, caste studies tell us more about the West than about India. It further demonstrates the imperative to move beyond this scholarship in order to generate descriptions of Indian social reality. The dominant descriptions of the 'caste system' that we have today are results of originally Christian themes and questions. The authors of this collection show how this hypothesis can be applied beyond South Asia to the diasporic cultures that have made a home in Western countries, and how the inheritance of caste studies as structured by European scholarship impacts on our understanding of contemporary India and the Indians of the diaspora. This collection will be of interest to scholars and students of caste studies, India studies, religion in South Asia, postcolonial studies, history, anthropology and sociology.
Keywords: Social sciences.; Religion and sociology.; Imperialism.; Social structure.; Social inequality.; Cultural studies.; Historical sociology.; Ethnicity.; elektronické knihy; electronic books